2019
DOI: 10.1039/c9nj01972c
|View full text |Cite
|
Sign up to set email alerts
|

A “turn-on” Michler's ketone–benzimidazole fluorescent probe for selective detection of serum albumins

Abstract: Enhanced emission and selective binding with albumins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Competitive binding studies showed that the probe selectively binds to albumin proteins over other substances commonly found in serum. Cellular imaging studies reveal localization in the cytoplasm, and serum depletion studies show a reduction in fluorescence intensity, indicating the probe's binding affinity to albumins 48 .…”
Section: Albumin Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Competitive binding studies showed that the probe selectively binds to albumin proteins over other substances commonly found in serum. Cellular imaging studies reveal localization in the cytoplasm, and serum depletion studies show a reduction in fluorescence intensity, indicating the probe's binding affinity to albumins 48 .…”
Section: Albumin Detectionmentioning
confidence: 99%
“…Cellular imaging studies reveal localization in the cytoplasm, and serum depletion studies show a reduction in fluorescence intensity, indicating the probe’s binding affinity to albumins. 48…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elegant examples based on small molecules illustrating not only the significant fluorescence sensing performance towards albumins but also the photostability, fluorescence quantum yields and fine-tuning the emission wavelengths to NIR region have been reported. [20][21][22][23][24][25] In parallel, the use of organic dye molecules such as functionalized squiraine, [26][27][28][29] cyanine, [30] fluorescein, [31] BODIPY dyes, [32,33] and others [34,35] have proven to be highly efficient for the detection and quantification of protein samples. Certainly, these BSA-dye interactions are useful for developing fluorescent markers, [29,36,37] protein assays, [31] and monitoring protease activity, [38] biophosphors, [39] solid-sate lightening (SSL) based on biomaterials, [40] and understanding the pharmacokinetics of albumin-based drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, stimuli-responsive turn-on fluorescent probes that can offer an easy and intuitive detection way with the naked eye directly are highly desired. [32][33][34][35] The user can quickly judge within an established detection range by the direct and time-saving lighton mechanism which is more in line with the industrial requirement.…”
Section: Introductionmentioning
confidence: 99%